Analisis Faktor-Faktor Yang Mempengaruhi Audit Delay (Studi Empiris pada Perusahaan LQ45) - Desiana, Desiana; Nanda, Ulfa Luthfia (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p10, 2022)
The purpose of this study is to analyze the effect of leverage, KAP reputation, audit committee, and complexity of operations, on audit delay. The population used in this study is LQ45 companies listed on the Indonesia Stock Exchange for 2016-2018, the sample was taken using purposive sampling with 84 observations. The analysis technique used in this research is multiple linear regression. The results showed that leverage had a negative effect on audit delay while the reputation of KAP, audit committee, operating complexity had no effect on audit delay. Keywords: Leverage; KAP Reputation; Audit Committee; Operation Complexity; Audit Delay